The Urgency of English Teaching in Private Primary School: Stakeholders’ Perceptions - Nida Husna; Genta Genta; Rifdatul Habibah; Farida Hamid; Didin Nuruddin Hidayat; Hesty Widiastuty (Jurnal Basicedu, 2022)
This research is aimed to find out the stakeholders’ perception regarding the urgency of English teaching in primary school, although English is not included as mandatory in the national curriculum of primary education level.  A qualitative approach was applied to the design of this descriptive study. The data were collected through questionnaires and semi-constructed interviews. The sample of this research consists of 12 teachers and 12 parents from 4 primary schools with different demographic areas. The findings were drawn out from depth analysis of data and a review of relevant pieces of literature on the research. It showed that the stakeholders have the same perception that English should be taught since primary school because it was their golden age to learn many things. It was also in agreement that English subject was needed to be taught in primary school since there are numerous advantages to learning English at early age.